Two MC1R loss‐of‐function alleles in cream‐coloured Australian Cattle Dogs and white Huskies. (22nd June 2018) - Dürig, N.; Letko, A.; Lepori, V.; Hadji Rasouliha, S.; Loechel, R.; Kehl, A.; Hytönen, M. K.; Lohi, H.; Mauri, N.; Dietrich, J.; Wiedmer, M.; Drögemüller, M.; et al.
Summary: Loss‐of‐function variants in the MC1R gene cause recessive red or yellow coat‐colour phenotypes in many species. The canine MC1R :c.916C>T (p.Arg306Ter) variant is widespread and found in a homozygous state in many uniformly yellow‐ or red‐coloured dogs. We investigated cream‐coloured Australian Cattle Dogs whose coat colour could not be explained by this variant. A genome‐wide association study with 10 cream and 123 red Australian Cattle Dogs confirmed that the cream locus indeed maps to MC1R . Whole‐genome sequencing of cream dogs revealed a single nucleotide variant within the MITF binding site of the canine MC1R promoter. We propose to designate the mutant alleles at MC1R :c.916C>T as e 1 and at the new promoter variant as e 2 . Both alleles segregate in the Australian Cattle Dog breed. When we considered both alleles in combination, we observed perfect association between the MC1R genotypes and the cream coat colour phenotype in a cohort of 10 cases and 324 control dogs. Analysis of the MC1R transcript levels in an e 1 /e 2 compound heterozygous dog confirmed that the transcript levels of the e 2 allele were markedly reduced with respect to the e 1 allele. We further report another MC1R loss‐of‐function allele in Alaskan and Siberian Huskies caused by a 2‐bp deletion in the coding sequence, MC1R :c.816_817delCT. We propose to term this allele e 3 . Huskies that carry two copies of MC1R loss‐of‐function alleles have a white coat colour.